Traction-assisted endoscopic full-thickness resection followed by O-ring and over-the-scope clip closure in the stomach: an animal experimental study - Kobara, Hideki; Nishiyama, Noriko; Fujihara, Shintaro; Tada, Naoya; Kozuka, Kazuhiro; Matsui, Takanori; Takata, Tadayuki; Chiyo, Taiga; Kobayashi, Nobuya; Fujita, Koji; Yachida, Tatsuo; Okano, Keiichi; Suzuki, Yasuyuki; Nishiyama, Akira; Mori, Hirohito; Masaki, Tsutomu (Endoscopy International Open, 2021)
Background and study aims Exposed endoscopic full-thickness resection (EFTR) enables the operator to obtain a sufficient surgical margin. However, insufflation leakage and secure endoscopic full-thickness closure (EFTC) remain problematic. This study aimed to evaluate the safety and feasibility of a new exposed EFTR.Patients and methods Exposed EFTR was performed for 2-cm virtual lesions in different locations of the upper stomach in four dogs. EFTR mainly involved half-circumferential EFTR of the endpoint and clip-line traction. Pulley traction was applied with the forward approach for the greater curvature. EFTC involved endoscopic ligation with O-ring closure to diminish insufflation leakage, followed by over-the-scope clip closure.Results Complete resection and technical success were achieved in all four cases. One case of intraoperative bleeding was endoscopically managed. No postoperative complications occurred in any cases. The median maximum resected size was 27.5 mm. The median procedure time of the total operation, EFTR, and EFTC was 76, 37, and 35.5 minutes, respectively. The 1-month survival rate was 100 %.Conclusions This therapeutic strategy may lead to the establishment of exposed EFTR.